2018
DOI: 10.1002/kin.21150
|View full text |Cite
|
Sign up to set email alerts
|

A Shock Tube Study of H Atom Addition to Cyclopentene

Abstract: We report shock tube studies of the kinetics of H atom addition to cyclopentene and modeling of the subsequent decomposition of cyclopentyl. Hydrogen atoms were generated with thermal precursors in dilute mixtures of cyclopentene and a reference compound in argon. Addition of H to the double bond leads to a cyclopentyl radical that rapidly ring opens and decomposes to ethene and allyl radical. The process was monitored by postshock gas chromatographic analysis of ethene and rate constants determined relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Rate constants involving the H precursors were likewise held constant. C 2 H 5 I chemistry has been extensively studied, 60,63,94–97 and we adopted the mechanism and rate constants from the detailed review of Bentz et al 60 HME decomposition has been frequently used at NIST for production of H atoms 53,65,98 . Tsang 52 has reported rate constants that are linked to standard reference reactions 46,55,58 and should be reliable.…”
Section: Modeling Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rate constants involving the H precursors were likewise held constant. C 2 H 5 I chemistry has been extensively studied, 60,63,94–97 and we adopted the mechanism and rate constants from the detailed review of Bentz et al 60 HME decomposition has been frequently used at NIST for production of H atoms 53,65,98 . Tsang 52 has reported rate constants that are linked to standard reference reactions 46,55,58 and should be reliable.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…C 2 H 5 I chemistry has been extensively studied, 60,63,[94][95][96][97] and we adopted the mechanism and rate constants from the detailed review of Bentz et al 60 HME decomposition has been frequently used at NIST for production of H atoms. 53,65,98 Tsang 52 has reported rate constants that are linked to standard reference reactions 46,55,58 and should be reliable. In the present work, the minor channel-producing propene from HME (R1543) impacts results under some of our conditions.…”
Section: And Propene (R1543)mentioning
confidence: 99%
“…Figure 3 illustrates a comparison of the different branching ratios; in this figure, R2 and R3, calculated at 1 atm, were gathered in order to compare with the C H and the C C β-scission routes. As can be seen from this figure, for Tsang 34 and Sirjean et al 11 the C H βscission pathway involving the formation of cyclopentene dominates over the temperature range of interest while for Manion and Awan 35 and for Sun et al 36 the C C β-scission channel (R2+R3) dominates. Intermediately, Al-Rashidi et al 5 calculated a crossover temperature (ca.…”
Section: Kinetic Modelingmentioning
confidence: 88%
“…The decomposition reactions by β-scission of the primary radicals of both fuels were also considered. β-Scission reactions involved in the consumption of cyclopentyl radicals were studied by several authors 5,11,34,35 with significantly different results in terms of branching ratios. For most of these authors, two pathways are considered: (i) the C H β-scission yielding cyclopentene from cyclopentyl (reaction R1) and (ii) the ring opening (C C β-scission) of cyclopentyl yielding pent-1-en-5-yl (reaction R2).…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…Recently, Al Rashidi et al [29] calculated the high-pressure limit rate constants of this reaction together with the C-H β-scission of cyclopentyl radicals at a high level of theory and determined subsequently the pressure-dependent rate constants based on the fall-off parameters from [30]. While Manion and Awan [43] reported that the C-C/C-H branching ratio of cyclopentyl radicals predicted by these rate constants [29] is still different from their experimental observation, these most recently calculated pressure-dependent rate coefficients are taken in the mechanism for the C-C and C-H β-scission reactions of hydroxycyclopentyl radicals.…”
Section: Ring-opening Reactions Of Hydroxycyclopentyl Radicalsmentioning
confidence: 99%